2018
DOI: 10.1186/s40425-018-0446-3
|View full text |Cite
|
Sign up to set email alerts
|

Mature dendritic cells correlate with favorable immune infiltrate and improved prognosis in ovarian carcinoma patients

Abstract: A high density of tumor-infiltrating CD8+ T cells and CD20+ B cells correlates with prolonged survival in patients with a wide variety of human cancers, including high-grade serous ovarian carcinoma (HGSC). However, the potential impact of mature dendritic cells (DCs) in shaping the immune contexture of HGSC, their role in the establishment of T cell-dependent antitumor immunity, and their potential prognostic value for HGSC patients remain unclear. We harnessed immunohistochemical tests and biomolecular analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
112
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(121 citation statements)
references
References 45 publications
9
112
0
Order By: Relevance
“…Mature DCs were able to induce the full complement of T cell activation, IFNγ production, T cell proliferation and development of cytotoxic T cells [23]. Naïve CD8 T cells do not produce large amounts of IFN-γ, but differentiation in CTLs is triggering the production of higher levels of the cytokine [24] [25]. In the present study, we observed that activated T cells with MUC1-pulsed DCs produced higher levels of IFNγ cytokine than naive CD8 T cells.…”
Section: Discussionsupporting
confidence: 55%
“…Mature DCs were able to induce the full complement of T cell activation, IFNγ production, T cell proliferation and development of cytotoxic T cells [23]. Naïve CD8 T cells do not produce large amounts of IFN-γ, but differentiation in CTLs is triggering the production of higher levels of the cytokine [24] [25]. In the present study, we observed that activated T cells with MUC1-pulsed DCs produced higher levels of IFNγ cytokine than naive CD8 T cells.…”
Section: Discussionsupporting
confidence: 55%
“…Similarly, although some reports attribute to robust infiltration by PD-1 þ cells a negative prognostic value, potentially linked to the highly exhausted status of these cells (14)(15)(16), other studies point to a rather beneficial effect (17,18), perhaps linked to the fact that CD103 þ PD-1 þ CD8 þ T cells appear to retain functional competence in the ovarian TME (19). We have recently demonstrated that CD20 þ B cells and DC-LAMP þ dendritic cells (DC) infiltrating HGSC lesions have a positive prognostic value as they orchestrate a T H 1-polarized immune response coupled to abundant CD8 þ CTL infiltration (5). However, the specific effect of PD-L1 levels and infiltration by immune cells expressing coinhibitory receptors on the composition and functional orientation of the TME in ovarian cancer patients, and how this influences disease outcome, remains to be clarified.…”
Section: Introductionmentioning
confidence: 98%
“…3,4). Moreover, abundant infiltration by CD8 þ cytotoxic T lymphocytes (CTL) as well as signs of a T H 1-polarized immune response is associated with improved disease outcome in a variety of tumors (2,(5)(6)(7). However, little is known about the impact of PD-L1 levels and tumor infiltration by immune cells expressing PD-1 and other coinhibitory receptors such as cytotoxic T lymphocyte-associated protein 4 (CTLA4), lymphocyte activating 3 (LAG-3), or hepatitis A virus cellular receptor 2 (HAVCR2, best known as TIM-3) on disease outcome in high-grade serous carcinoma (HGSC) patients.…”
Section: Introductionmentioning
confidence: 99%
“…The presence of activated, mature dendritic cells (CD107a + DCs) in the ovarian cancer TME is correlated with a better prognosis [54]. They attract anti-tumour cell subsets (cytotoxic T lymphocytes (CTLs) and natural killer (NK) cells) but also pro-tumour cells (tumour-associated macrophages (TAMs), myeloid-derived suppressor cells (MDSCs) and regulatory T cells (Tregs)) to the TME.…”
Section: Figurementioning
confidence: 99%